2021
DOI: 10.1002/lio2.618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of percutaneous injection laryngoplasty on voice and swallowing problems in cancer‐related unilateral vocal cord paralysis

Abstract: Background Unilateral vocal cord paralysis may result from nerve compression by tumors or direct nerve injuries during tumor resections, which can cause dysphonia or dysphagia, and reduced quality of life. Objectives This prospective, single‐group study aimed to investigate the effect of percutaneous injection laryngoplasty on voice and swallowing function in patients with cancer‐related unilateral vocal cord paralysis. Methods Patients underwent percutaneous injection laryngoplasty with hyaluronic acid under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…Also, there was no significant difference between either group regarding presence of residue 1week and 3 months postintervention. This is in agreement with Kang et al [17] who reported by videofluoroscopic dysphagia scale that no significant improvement in presence of vallecular or pharyngeal residue because IML improves glottic incompetence, but injection laryngoplasty (IL) cannot enhance the sensory abnormalities of the larynx owing to the inconsistent timing of the procedure. Patients who got injectable laryngoplasty after 8 weeks of symptoms start demonstrated more significant improvements compared to those who underwent the surgery after 8 weeks or longer.…”
Section: Discussionsupporting
confidence: 92%
“…Also, there was no significant difference between either group regarding presence of residue 1week and 3 months postintervention. This is in agreement with Kang et al [17] who reported by videofluoroscopic dysphagia scale that no significant improvement in presence of vallecular or pharyngeal residue because IML improves glottic incompetence, but injection laryngoplasty (IL) cannot enhance the sensory abnormalities of the larynx owing to the inconsistent timing of the procedure. Patients who got injectable laryngoplasty after 8 weeks of symptoms start demonstrated more significant improvements compared to those who underwent the surgery after 8 weeks or longer.…”
Section: Discussionsupporting
confidence: 92%
“…Prior studies offer a wide range of follow‐up times between IL and instrumental swallowing assessments, ranging from days to years. 10 , 13 , 14 , 15 , 17 Ultimately, there has been no clear data on the anticipated time to aspiration recovery for vocal cord injection pediatric patients. This timeline variability can distort improvement percentages, as children may naturally experience a spontaneous improvement in dysphagia and vocal cord function over time without interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, although better glottic closure could theoretically contribute to better swallowing function, limited literature has assessed swallowing pathology after medialization surgery on patients with UVFP. Particularly, few studies reported the swallowing impact of ML + AA on patients with UVFP while recent several studies assessed the effectiveness of IL on swallowing function 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…Particularly, few studies reported the swallowing impact of ML + AA on patients with UVFP while recent several studies assessed the effectiveness of IL on swallowing function. [8][9][10][11] In this study, we evaluated swallowing function before and after vocal fold medialization surgery in patients with UVFP. Furthermore, we comparatively analyzed the differences in swallowing impact between IL and ML + AA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation